(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Yolde Formation conformably overlies the Bima Sandstone. It is Cenomanian in age and marks the onset of marine transgression into the Gongola sub basin of the Benue Trough. Comprises mainly of sandstones, limestone, shales, clays and claystones. The study section exposed about 70m thick of the Yolde Formation along Pantami stream channel, Gombe, Gombe town. Several lithofacies of sandstones and mudstones ware identified. The sandstones vary from very fine, fine, medium to coarse grained. Sedimentary structures identified include parallel, planar cross- beddings, trough cross-beddings and herringbone cross-stratification. Lithofacies analysis shows series of fining and coarsening upward sequences which indicate increase and decrease in depositional energies within the environment. Petrographic analysis shows that the sandstone samples are texturally matured. The Quartz grains are both monocrystalline and polycrystalline in nature while the sub-rounded to rounded nature of the grains suggests that the sediments were transported from a long distance. The framework components of the sandstones based on the QFR plot shows that the sandstones are Quartzarenite, Sublitharenite to Litharenite and Subarkorse to Arkosic in nature. Grainulometric analysis shows that the sandstones are moderately to poorly sorted (1.0-2.0)∂I, the grains sizes are fine to medium (2.7-0.9)MZ platykurtic to very leptokurtic (0.9-1.9)KG and are coarse to strongly fine skewed (0.04-0.6)SKI. From the histograms, the sediments are generally unimodal indicating the same sources of sediments, typical of fluvial environment. Also, the poor sorting and fine skewness is as a result of increase and decrease in depositional energies by river/wave processes which was further buttressed by bivariate plots. Porosity of the samples assessed indicate moderate to good porosity and the permeability assessment indicate moderate to good permeability as well.